2019
DOI: 10.1108/jfm-10-2017-0051
|View full text |Cite
|
Sign up to set email alerts
|

A literature review of routine maintenance in high-rise residential buildings

Abstract: Purpose Facilities management plays a significant role in the housing industry to support human daily routine and enhancing the productivity of the activities in and around the residential. Nonetheless, facilities management has not been readily encouraged or adopted by the Government in Malaysia in any structured way. The maintenance approaches adopted are mostly corrective which resulting poor service delivery, poor user satisfaction and endless maintenance backlogs. Thus, this paper aims to review the imple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 76 publications
(86 reference statements)
0
20
0
Order By: Relevance
“…Maintenance organisations that failed in preventive maintenance adoption face high maintenance problems. For example, the building performance will be low for those buildings which are maintained by organisations that failed to adopt preventive maintenance (Lateef, 2009;Khalil et al, 2016;Au-Yong et al, 2019). Moreover, a lack of preventive maintenance execution leads to unbudgeted expenditure and has an impact on the total funds allocated to the maintenance, which leads to unavailability of supplies, in most cases, to carry out maintenance tasks (Ali and Mohamad, 2009).…”
Section: Building Maintenance Practices Issues and Effectsmentioning
confidence: 99%
“…Maintenance organisations that failed in preventive maintenance adoption face high maintenance problems. For example, the building performance will be low for those buildings which are maintained by organisations that failed to adopt preventive maintenance (Lateef, 2009;Khalil et al, 2016;Au-Yong et al, 2019). Moreover, a lack of preventive maintenance execution leads to unbudgeted expenditure and has an impact on the total funds allocated to the maintenance, which leads to unavailability of supplies, in most cases, to carry out maintenance tasks (Ali and Mohamad, 2009).…”
Section: Building Maintenance Practices Issues and Effectsmentioning
confidence: 99%
“…Issues of building maintenance are one of the challenges facing building maintenance success. Au-Yong et al (2019) found that building maintenance issues continue to increase in recent years. These buildings may be aged.…”
Section: Introductionmentioning
confidence: 99%
“…The GPUR is framed on an RM basis, which is essential to keep buildings functional and protected against early decay. A content analysis of reviewed publications accomplished by Au-Yong et al (2019) confirms that RM of facilities and building services is essential and it plays a vital role towards the maintenance outcomes. Thus, management entities, which invest in RM can extend the life of their assets, reduce reactive maintenance and keep their facilities up and running more reliably.…”
Section: Streamline Building Operationmentioning
confidence: 85%
“…4.2.3.1 Cleaning. Cleaning maintenance is an on-going process to sustain cleanliness and it is essential for keeping the building condition at a high appearance level (Au-Yong et al, 2019). It is an efficient way to keep indoor environments sustainable, healthy and sanitary.…”
Section: Streamline Building Operationmentioning
confidence: 99%